Active targeting of cancer cells by CD44 binding peptide-functionalized oil core-based nanocapsules. Issue 40 (13th July 2021) - De Capua, A.; Palladino, A.; Chino, M.; Attanasio, C.; Lombardi, A.; Vecchione, R.; Netti, P. A.
Abstract : CD44 binding peptide was implemented onto an oil core–polymer multilayer shell of 100 nm size and completely biodegradable. Biological tests, demonstrated that the proposed nanocarrier selectively accumulates and internalizes in cancer cells. Abstract : Selectivity in tumor targeting is one of the major issues in cancer treatment. Therefore, surface functionalization of drug delivery systems with active moieties, able to selectively target tumors, has become a worldwide-recognized strategy. The CD44 receptor is largely used as a biomarker, being overexpressed in several tumors, and consequently as a target thanks to the identification of the CD44 binding peptide. Here we implemented the CD44 binding peptide logic onto an oil core–polymer multilayer shell, taking into account and optimizing all relevant features of drug delivery systems, such as small size (down to 100 nm), narrow size distribution, drug loading capability, antifouling and biodegradability. Besides promoting active targeting, the oil core-based system enables the delivery of natural and synthetic therapeutic compounds. Biological tests, using curcumin as a bioactive compound and fluorescent tag, demonstrated that CD44 binding peptide-functionalized nanocapsules selectively accumulate and internalize in cancer cells, compared to the control, thanks to ligand–receptor binding.